SARS-CoV-2 infection triggers profibrotic macrophage responses and lung fibrosis - Wendisch, Daniel; Dietrich, Oliver; Mari, Tommaso; Von Stillfried, Saskia; Ibarra, Ignacio L.; Mittermaier, Mirja; Mache, Christin; Chua, Robert Lorenz; Knoll, Rainer; Timm, Sara; Brumhard, Sophia; Krammer, Tobias; et al. (Cell, 2021)
COVID-19-induced “acute respiratory distress syndrome” (ARDS) is associated with prolonged respiratory failure and high mortality, but the mechanistic basis of lung injury remains incompletely understood. Here, we analyze pulmonary immune responses and lung pathology in two cohorts of patients with COVID-19 ARDS using functional single-cell genomics, immunohistology, and electron microscopy. We describe an accumulation of CD163-expressing monocyte-derived macrophages that acquired a profibrotic transcriptional phenotype during COVID-19 ARDS. Gene set enrichment and computational data integration revealed a significant similarity between COVID-19-associated macrophages and profibrotic macrophage populations identified in idiopathic pulmonary fibrosis. COVID-19 ARDS was associated with clinical, radiographic, histopathological, and ultrastructural hallmarks of pulmonary fibrosis. Exposure of human monocytes to SARS-CoV-2, but not influenza A virus or viral RNA analogs, was sufficient to induce a similar profibrotic phenotype in vitro. In conclusion, we demonstrate that SARS-CoV-2 triggers profibrotic macrophage responses and pronounced fibroproliferative ARDS.
CRIS-Team Scopus Importer:2023-03-08
Keywords: ARDS; COVID-19; fibrosis; IPF; lung; macrophages; monocytes; proteomics; pulmonary fibrosis; SARS-CoV-2; single-cell transcriptomics